Two-stage Revision Total Knee Arthroplasty Using a Prefabricated Antibiotic-impregnated Articulating Spacer - Sankalp Lal; Pankaj Kumar Damor; Mukesh Kumar Saini; Ramniwas Bishnoi; Mahesh Bhati (Journal of Orthopedics, Traumatology and Rehabilitation)
Periprosthetic joint infection (PJI) is one of the most dreaded complications following total knee arthroplasty (TKA). Even though the incidence is low following TKA, it still constitutes a large number of cases due to increasing rates of TKA. Two-stage revision TKA using a prefabricated antibiotic-impregnated articulating methyl-methacrylate spacer offers eradication of infection along with the additional advantage of improved interval/postrevision function and range of motion compared to custom-made/static spacers and should be considered the treatment of choice for chronic PJI.